COVID-19 pandemic: protective role of vitamin D - O. A. Gromova; I. Yu. Torshin; G. Kh. Gabdulina (Фармакоэкономика)
Introduction. The COVID-19 pandemic revealed the vulnerability of the general population to this infectious disease, which is determined by the lack of immunity to the new SARS-CoV-2 coronavirus and is characterized by cytokine storm in severe cases. One of the most important reasons for this vulnerability is a high occurrence rate of micronutrient deficiencies, and above all, vitamin D deficiency.Aim. To systematize the available data on the role of vitamin D in the prevention of COVID-19 infection.Materials and methods. Systematic computer analysis of the entire array of available scientific publications on coronaviruses (21,300 publications in PUBMED and preprint repositories, including 7,500 publications on COVID-19 and SARS-CoV-2) was performed. The methods of topological and metric data analysis were used. About 50 most informative sections were identified that were mainly associated with COVID-19 / SARS-CoV-2. The analysis of the obtained “map” of molecular pathophysiology of COVID-19 was performed.Results. Vitamin D activates the expression of many genes involved in supporting the immunity against coronaviruses and other singlestranded RNA viruses (interferon-dependent protection). The results of the systematic analysis of the publications on coronavirus showed that vitamin D is important for attenuating the effects of the cytokine storm and compensating for chronic comorbid pathologies.Conclusion. The compensation for vitamin D deficiency is an essential component of COVID-19 prevention. This tactics of prevention is less costly than managing patients with severe forms of COVID-19 and can help save public healthcare resources.